Ethnopolitic problems of modern Dagestan - Roman Al'bertovich Amburtsev; Sergey Andreevich Khrushchev (Наука. Инновации. Технологии)
The multinational structure of the population of Dagestan objectively causes need to lead effective state national policy. In the political sphere it has led to creation of system of informal ethnic hierarchy in public authorities which in modern conditions demands its modernization. Still open is a question of real, but not formal allocation Dagestan's autochthonous minorities. Important problem is presence of the divided ethnoses by frontier with Azerbaijan. With a growth of a share of autochthonous ethnoses in the population of Dagestan there is strengthening of their migratory outflow from Republic. Mass migratory outflow and depopulation of the Russian population have led to practical elimination of once representatively Russian community in Dagestan.